EVALUASI KERENTANAN GEDUNG REKTORAT STTNAS TERHADAP GEMPA BUMI BERDASARKAN ANALISIS MIKROTREMOR - Prastowo, Rizqi; Prabowo, Urip Nurwijayanto (Sekolah Tinggi Teknologi Adisutjipto, 2017)
STTNAS building is a five floor building that located in the city o f Yogyakarta which is an area with a high intensity earthquake occurrence. The purpose o f this study is (1) determine the value o f the natural frequencies o f the building, (2) determine the index o f the resonance o f the building and (3) the vulnerability o f buildings to earthquakes. Research will be done by measuring the microtremor wave o f building STTNAS then analyzed using Spectral Floor Ratio (FSR). The analysis result is then compared with the classification defined in ISO 2002 on building resilience planning procedures earthquake. Fekuensi natural on the east-west component is 1.64 Hz and the north-south component is 1.644 Hz that is in conformity with the ISO 2002. Resonance Index o f building STTNAS is ranging from 31.00081 to 35.883% thus including the low category resonance during an earthquake. Building of STTNAS vulnerability index ranges are between 103,670.6191 to 82526.5357 with the highest value found on the 4th floor.